Boosting the optical properties of polylactic acid/ lanthanide-based metal-organic framework composites. (April 2023) - Simões, R.; Rodrigues, J.; Granadeiro, C.M.; Rino, L.; Neto, V.; Monteiro, T.; Gonçalves, G.
Abstract: Luminescent lanthanide metal-organic frameworks (LnMOF) are gathering much interest in the scientific community due to their exceptional optical properties, which have the potential to revolutionize several application fields, including anti-counterfeiting. The traceability of the original products is an ever-growing demand for producers and end-users to verify the authenticity of produced goods. Following this newfound need, we propose an anti-counterfeiting method based on a quick-response (QR) code, with a very specific verification procedure, using a luminescent LnMOF-based composite. The embedded code will only react to certain stimulation, hence it can only be unlocked using the sequence that is programmed to respond to. For that purpose, we explored the incorporation of fresh LnMOFs, with europium (EuMOF) and terbium (TbMOF), on a biodegradable polymer matrix of polylactic acid (PLA). A homogeneous mixture of PLA/LnMOF was produced via a two-step process including solvent casting followed by thermal mixing, after achieving the optimized concentration for each filler. The optical characterization of the fresh composites showed an excellent response to selective excitation, with well-defined intraionic lines for TbMOF @ 542 nm ( 5 D4 → 7 F5 ) and for EuMOF @ 615 nm ( 5 D0 → 7 F2 ). PLA/Eu, TbMOF composites were also explored to create an additional level of encryption by tuning the emitted color with the appropriate excitation stimuli. Hence, these new luminescent composite materials can be used as traceable optical tags for a wide variety of polymeric products, capable to respond to a very specific excitation wavelength and act as a level three luminescent security marker, whose decoding demands the assessment of more than one factor, with near-impossible replication. Additionally, this technology has a high potential for scalability since the applied processing techniques used for the production of the optically active QR code are commonly employed in the polymer industry. Nevertheless, the analysis of the aged effects clearly indicates the need for a definition of new strategies to enhance the efficiency of the sensitization process of the Ln 3+ intraionic emission. Graphical abstract: Image 1